Genetic Diagnosis of Rubinstein–Taybi Syndrome With Multiplex Ligation-Dependent Probe Amplification (MLPA) and Whole-Exome Sequencing (WES): Case Series With a Novel CREBBP Variant - Lee, Yu-Rong; Lin, Yu-Chen; Chang, Yi-Han; Huang, Hsin-Yu; Hong, Yi-Kai; Aala, Wilson Jr F.; Tu, Wei-Ting; Tsai, Meng-Che; Chou, Yen-Yin; Hsu, Chao-Kai (Frontiers in Genetics, 2022)
Rubinstein–Taybi Syndrome (RSTS) is a rare congenital disease with distinctive facial features, broadening of the thumbs and halluces, and developmental delay. RSTS is caused by de novo genetic alterations in CREBBP and the homologous EP300 genes. In this study, we established a genetic diagnostic protocol by integrating multiplex ligation-dependent probe amplification (MLPA) and whole-exome sequencing (WES). Five patients clinically diagnosed with RSTS were enrolled for genetic testing. Germline DNA was extracted from the peripheral blood of the patients and their families. One patient (Case 1) was identified as harboring a large heterozygous deletion in the 16p13.3 region, spanning the CREBBP gene. Three patients (Cases 2–4) harbored different CREBBP variants (c.2608C>T:p.Gln870Ter, c.4404_4405del:p.Thr1468fs, c.3649C>T:p.Gln1217Ter). No causative variants were identified for the fifth RSTS patient (Case 5). Here, we propose a molecular diagnostic protocol that identified causative genetic alterations in 4/5 of the patients, yielding a molecular diagnostic rate of 80%. Given the rarity of RSTS, more research is needed to explore its pathogenesis and mechanism.